2021
DOI: 10.1111/jcpe.13525
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density is associated with severe periodontitis at the end of the second decade of life: A population‐based study

Abstract: Aim: To evaluate the association between low bone mineral density (BMD) and severe periodontitis at the end of the second decade of life.Materials and methods: This population-based study analysed 2032 youngers (18-19 years old) of the RPS cohort. BMD of lumbar spine (BMD-LS) and of the whole body (BMD-WB) were assessed by dual x-ray emission densitometry. Low BMD-LS (Z-score ≤ À2) and low BMD-WB (Z-score ≤ À1.5) were correlated with severe periodontitis. The extent of periodontal disease was also evaluated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…The decreased mass and fragility of the alveolar bone were prone to facilitate oral biofilm infection, spell host immunological responses, and accelerate the progression of periodontitis. [39] In our case, vitamin D supplementation proved to be useful in treating periodontitis adjunctively, which is consistent with the studies reported before. [16,40] With the combination of scaling and root planing and vitamin D supplementation, the periodontal condition has improved.…”
Section: Authorsupporting
confidence: 92%
“…The decreased mass and fragility of the alveolar bone were prone to facilitate oral biofilm infection, spell host immunological responses, and accelerate the progression of periodontitis. [39] In our case, vitamin D supplementation proved to be useful in treating periodontitis adjunctively, which is consistent with the studies reported before. [16,40] With the combination of scaling and root planing and vitamin D supplementation, the periodontal condition has improved.…”
Section: Authorsupporting
confidence: 92%
“…According to epidemiological studies, early signs of incipient periodontitis unnoticeably become widespread and severe irrespective of the age group (López et al, 2009). Furthermore, this greater periodontal destruction in young subjects can be explained by systemic disequilibrium of the host, such as alterations in the bone metabolism (Costa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have found that high levels of glycine might decrease the bone mineral density (BMD), thus increasing the risk of osteoporosis (Eriksson et al 2021;Zhang et al 2021). Considering that low BMD is a risk factor for severe periodontitis (Costa et al 2021), we speculate that the increase of glycine may increase the risk of periodontitis and lead to tooth loss by decreasing alveolar BMD. However, direct evidence for this relationship is lacking, so the effect of glycine on the risk of tooth loss needs further study.…”
Section: Discussionmentioning
confidence: 99%